Determinants Of The Decision Of Indonesian Workers (Tki) To Become Customers At Bank Syariah Indonesia - Faqih El Wafa (Publikasi Indonesia, 2023)
Hamlet, it can be concluded that Ampeldento Hamlet has a large area of 8x6m2 for a capacity of 5 service personnel. The service room has service tables, activity tables, 2 sets of Electronic Community Identity Card recording equipment, and remote benches intended for residents waiting for services. The Ampeldento Hamlet office does not yet have sufficient service facilities to provide services to residents such as at least a chair in the waiting room, there is no table for writing in the waiting room, and data tools do not yet exist. Facilities such as generators are not maximized, so when the electricity goes out, the service process will also stop everything, which means residents cannot get services. Hamlet Ampeldento in terms of reliability (reliability) in terms of reliability